(untitled) (National Administration Journal, 2019)
The inability to respond to organizational demands resulting from its exercise can lead to psychosocial risk factors such as stress. The objective of this study was to assess the perception of management and business professionals about some organizational variables as potential sources of work stress. The Questionnaire for the assessment of factors that generate stress in organizations (CUVEO) was designed and applied.The instrument was appliedin a sample of 784 male and female subjects between19 and 70 years of age with minimal schooling of incomplete university (Most of them with complete college) The data was analyzed using the SPSS software (for its acronym in English). In general terms,the assessment of the participants’perception of the variables investigated as potential generators of stress has resulted in a medium level, which refers to the importance of attention to their scope.